Estratégias para a construção de uma cultura de acessibilidade atitudinal no curso de Licenciatura em matemática da UFPA - RODRIGUES, Giliardo dos Santos (2023)
The main objective of this work is to reflect on the strategies that can be adopted in the construction of a culture of attitudinal accessibility in the degree course in Mathematics at UFPA. For this, an introductory study was carried out on some historical aspects and about the legislation of inclusive education, in addition to the dimensions and conceptions of accessibility. We also investigated how attitudinal accessibility happens in higher education institutions. In researching possible strategies for the construction of a culture of attitudinal accessibility, we sought in the literature some theorists who study the subject and also some reports of experiences carried out by institutions of higher education. Furthermore, we highlight how art, in particular cinema, can contribute to promoting attitudinal accessibility. The research methodology is a qualitative approach using bibliographical and documental research techniques.